Mental health challenges in professional musicians: a systematic review of stress, anxiety, and depression - Cardoso, Mário (2025)
Mental health challenges among professional musicians have gained attention due to the unique stressors associated with their careers. This review provides a comprehensive overview of these challenges and identifies potential areas for further research and intervention. A systematic search was conducted across multiple databases, including PubMed, Scopus, and Web of Science, using keywords such as "mental health," "musicians," "professional musicians," "stress," "anxiety," "depression," and "psychological well-being." The findings highlight the multifaceted nature of Music Performance Anxiety (MPA), influenced by psychological, physiological, and environmental factors. Interventions such as Cognitive Behavioral Therapy (CBT), biofeedback, and structured programs like ConfiDance show promise in reducing MPA and enhancing performance. However, additional research is needed to develop interventions tailored to musicians of different skill levels and genres. Further studies should also explore personality traits, performance settings, and long-term coping mechanisms for comprehensive support. The review underscores the significant mental health challenges musicians face, including high levels of stress, anxiety, and depression. The demanding nature of their profession—marked by performance pressure, irregular schedules, financial instability, and social isolation—contributes to these issues, potentially affecting creativity and career longevity. Addressing these challenges through targeted interventions is crucial for supporting musicians' mental well-being.